(untitled) (Numerus academy review, 2026)
The dominance of images and illustrations is evident in the different textbooks, especially the elementary school section books, which encompass various activities and different information, and which are crowned with expressive images and different designs to be closer to the imagination and psychology of the child, and more persuasive in the transmission of ideas and the achievement of the desired objectives of each activity, such as Social, , religious and humanitarian education so that he’d have an effective role in his society, , and as a consequence, the image took the place of the word to become a means and an end in itself, because it is a means of teaching the language to the learning child,of transmitting new knowledge to him and to get him to express his opinion, and an end because it is fun and exciting for The Young Learner, because such images bring him pleasure and catch his attention. Therefore, this study aims to discover the most important characteristics of the educational image in particular, and to try to provide the child with a language through it. The problems were as follows : 1-What are the characteristics of the educational image? 2-What is the relationship between image and language learning? 3- Does the quality of the educational images affect the correctly acquired language and the psyche of the learner?